Pengaruh Air Laut sebagai Air Pencampur dan Air Perawatan pada Karakteristik Pasta Semen dan Mortar - Ali, Adiwijaya; Datu, Irka Tangke (INTEK: Jurnal Penelitian, 2018)
The goal of this research is to investigate the influence of seawater as mixing water and curing water on characteristics of cement paste and mortar. Research was conducted with making mixtures of cement paste and mortar using two kind of cement, Portland Composite Cement (PCC) and Pozzolana Portland Cement (PPC) with seawater as mixing water. Characteristics of fine aggregate and characteristics of cement paste with seawater mixing were investigated. Furthermore, 144 cube mortar specimens in size of 5 cm x 5 cm x 5 cm in four series mortar mixtures were casted according with SNI 03-6825-2002. At 24 hours after specimens were casted, cube mortar specimens were cured in tap water curing (TC), seawater curing (SC) and air curing (AC). After achievement at certain curing day of 3, 7, 14 and 28 days, cube mortar samples were tested in compressive strength. Results concluded that seawater mixing improves compressive strength of mortar up to 28 days in all curing conditions, TC, SC and AC. Moreover, strength of mortar is not affected by type of curing water, tap water or seawater.